2022
DOI: 10.3390/jrfm15020086
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impact of Legal Regulation on Financial Security in OECD Countries

Abstract: The recurrent economic and financial crises expose the state, enterprises, and households to a range of financial risks and negative financial consequences. As a result, governments are seeking the most efficient measures of legal regulation and other measures ensuring financial security in order to address financial insecurity. The financial security can be considered from a variety of perspectives, and this research proposes that microeconomic and macroeconomic indicators be taken into account when assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The results of the authors' study Vaitkus R. et al (2022) confirmed that legal regulation has a significant positive impact on financial security. Based on the results of the study, the authors claim that legal regulation, in particular anti-corruption measures, should be an integral part of the financial security strategies that are being developed.…”
Section: Literature Reviewsupporting
confidence: 53%
“…The results of the authors' study Vaitkus R. et al (2022) confirmed that legal regulation has a significant positive impact on financial security. Based on the results of the study, the authors claim that legal regulation, in particular anti-corruption measures, should be an integral part of the financial security strategies that are being developed.…”
Section: Literature Reviewsupporting
confidence: 53%
“…In the academic literature, both Russian and foreign authors most often consider the concept of economic security, while some authors associate the regional financial security with the risks of threats at strategically important enterprises (Korableva et al, 2020), in other studies, financial security is presented as a component of the economic security of the state/region (Borsch and Gerasimova, 2018, Anofrikov et al, 2018, Dankiewicz et al, 2021, Haber et al, 2018, Han, 2018, Grikietytė-Čebatavičienė, 2021, Prado, 2018, Rasdi et al, 2021, Rodica et al, 2014, Vaitkus and Vasiliauskaite, 2022. Table 1 presents the most common approaches to the definition of the concept of "financial security".…”
mentioning
confidence: 99%